Young Fu of the upper Yangtze - Lewis, Elizabeth Foreman 1892-1958.; Low, William (New York Henry Holt, 2007)
In the 1920's, a Chinese youth from the country comes to Chungking with his mother where the bustling city offers adventure and his apprenticeship to a coppersmith brings good fortune.
"75th anniversary edition with new illustrations by William Low"--Cover p. 2.
Keywords: City and town life -- China -- Juvenile fiction; City and town life -- China -- Fiction; China -- Juvenile fiction; China -- Fiction